PERTANGGUNGJAWABAN PIDANA TERHADAP TNI PANGKAT TITULAR YANG MELAKUKAN PELANGGARAN HUKUM - Yusep Mulyana (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
The reason is that civilians without official military missions like Deddy Corbuzier can be awarded the title of Lieutenant Titular. The awarding of the rank of Titular Lieutenant Colonel to celebrity Deddy Corbuzier (DC) is related to his ability to communicate on social media to spread national messages. Deddy was given this rank with the consideration of the special capabilities needed by the TNI, namely communication capacity on social media, capabilities, and the DC 'performance' will help the TNI to spread national messages and socialize the TNI's duties in the context of maintaining the Republic of Indonesia's defense. Criminal Liability Against Titular Rank Armed Forces Committing Law Violations is the imposition of military discipline applicable to the military or people who are equated with the military for their actions, and military law applies and settlement in military courts.